2012
DOI: 10.1111/j.1442-2018.2012.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance care practices in complementary and alternative medicine by Thai breast cancer survivors: An ethnonursing study

Abstract: The purpose of this study was to explore how Thai breast cancer survivors perform care practices in complementary and alternative medicine to promote their health and well-being. Research was conducted using an ethnonursing method. Data were collected through semi-structured interviews with 17 Thai breast cancer survivors in Thailand. The transcribed interviews were analyzed using the ethnonursing analysis method. The findings showed Thai breast cancer survivors started their care practices in complementary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…There is also increasing trend that complementary and alternative medicine (CAM) became popular worldwide[23], [24]. Recently, the alternative therapies on cancer care became more popular and acceptable in the world[25], [26] including complementary medicine or supportive therapy such as MT or massage[27]. However, many adverse effects concerning the possibility to promote metastasis have been reported[6], [9], [28].…”
Section: Discussionmentioning
confidence: 99%
“…There is also increasing trend that complementary and alternative medicine (CAM) became popular worldwide[23], [24]. Recently, the alternative therapies on cancer care became more popular and acceptable in the world[25], [26] including complementary medicine or supportive therapy such as MT or massage[27]. However, many adverse effects concerning the possibility to promote metastasis have been reported[6], [9], [28].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients use CAM more often than patients with other types of cancer due to treatment side effects and problems continuing after treatment [68]. Wanchai et al [68] found that among Thai survivors, CAM information is obtained through peers and only one-third of Thai breast cancer survivors report sharing information about CAM usage with their physicians due to their fear of a negative response.…”
Section: Managementmentioning
confidence: 99%
“…The similarities in both studies included use of CAM by all informants, stage of survivorship (range of extended to long-term survivors), an emic view of CAM as a holistic approach, and some of the factors influencing CAM use (importance of family and friends); and getting information about CAM (Wanchai et al, 2010(Wanchai et al, , 2012. Other researchers using a variety of quantitative methods have had similar findings in U.S. and Malay breast cancer survivors in terms of CAM use, multiple factors for using CAM, sources of information, and reluctance by some to discuss their use with physicians (Carpenter et al, 2009;Matthews et al, 2007;Shaharudin, Sulaiman, Emran, Shahril, & Hussain, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study (Wanchai et al, 2010) included two interview sessions (60-to 90-minute range). The remaining two studies indicated data collection procedures included one interview (30-to 60-minute range) per informant (Wanchai et al, 2011(Wanchai et al, , 2012. The one-time, shorter interview suggests limited engagement with informants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation